Drying Temperature and Hornification of Industrial Never-Dried Pinus radiata Pulps. 1. Strength, Optical, and Water Holding Properties - Dante E. Giacomozzi; Olli Joutsimo (BioResources, 2015)
Hornification and changes in properties of bleached Pinus radiata pulps were studied for oven-dried pulps and compared to never-dried pulps. Evaluation of unrefined and PFI-refined pulps showed an increase in strength loss with high drying temperature. The tensile index was reduced by 40 to 55%, the tear index was reduced by 14 to 31%, and the degree of hornification, measured as WRV, increased from 25 to 34% when the drying temperature was increased from 25 °C to 130 °C. The tensile stiffness index, Scott bond, and elongation were reduced, whereas the bulk, opacity, air permeability, and light scattering values increased at high drying temperatures. Neither fiber deformations nor damages were observed to justify such reductions in strength properties. In PFI refining, pulps dried at 130 °C required three times more revolutions than never-dried pulps to develop tensile index until 70 Nm/g. Dried pulps were found to have less capability to hold water into the fibers’ pore structure, as shown by water retention value. Changes in Scott bond, bulk, and water retention value suggested that besides irreversible pore closure and fibril microfibril aggregation, delamination can contribute to the observed strength loss in dried compared to never-dried pulps.